Comparative Analysis of Educational Financing Systems Across Countries - Husnul Hatimah; Ridwan Idris; Mardyawati Yunus (Journal of Educational Management Research, 2026)
This study aims to analyze and compare education financing systems in Finland, Japan, the United States, and Indonesia, with a focus on identifying key characteristics, philosophical differences, and policy implications of each model. The research employs a systematic literature review combined with comparative analysis, using management-oriented indicators including equity, efficiency, governance, and sustainability. Findings indicate that Finland implements a full public funding model emphasizing equity, Japan operates a hybrid model with high transparency, the United States exhibits significant disparities due to property-tax-based decentralization, and Indonesia remains in a transitional phase with challenges in fiscal capacity and governance accountability. The study highlights that successful education financing depends on consistent policy implementation, clear funding distribution formulas, and integrity in governance systems. The results provide actionable policy implications for improving national education financing, including the adoption of needs-based funding formulas, digitalized accountability systems, and diversified funding sources through public–private partnerships. By integrating management and governance dimensions, this study contributes to a better understanding of effective and equitable educational funding practices across diverse contexts.